CHARGE CARRIERS STATES IN A MODEL OF CuO SUPERCONDUCTIVE CERAMICS - Jovan Šetrajčić; Siniša Vučenović (Journal of Sustainable Technologies and Materials)
The translational symmetry of the distribution of atoms (ions) of the charge carriers (electrons or holes) system is broken by sputtering (doping) due to the existence of two boundary surfaces. This is a model of high-temperature superconductors in which the observed symmetry breaking orthogonal to the CuO plane is treated as a perturbation. Single-particle fermion wave functions and possible charge carrier energies were determined. The competing existence of superconducting and normal regions in such a sample is shown in agreement with experimental data. The conditions for the formation of superconducting states and the limits of the current density values in the planes parallel to the boundary surfaces (in the CuO planes) were obtained and discussed.